PENGARUH SKARIFIKASI TERHADAP VIABILITAS DAN VIGORITAS BENIH KELOR (Moringa oleifera) PADA SKALA RUMAH KACA - Aulia Vivi Zulaiha; Ubaidillah Ubaidillah; Rahmi Dianita (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2020)
Scarification is a technique to physically damage the seed coat to reduce hard seed (while keeping the seed viable) and increase water imbibition into the seed in order to increase seed germination. This study aims to determine the effect of mechanical scarification on the viability and vigor of Moringa oleifera seeds. A greenhouse scale experiment was conducted at the Faculty of Animal Science, University of Jambi for one month. The experiment was arranged in a Completely Randomized Design (CRD) consisted of 4 treatments and 5 replications. The treatments were P0 = seed without scarification (control), P1 = seed rubbed on one side, P2 = seed rubbed on two sides and P3 = seed rubbed on three sides - the entire surface of the seed. The seeds have 7-8% moisture content and rubbed with sandpaper. Variables observed were germination rate, germination speed, simultaneity of germination, normal sprout dry weight as a viability variable, and number of leaf sub branches and plant dry weight as vigority variable. The results showed that scarification on the three side (on entire seeds coat) was very significantly (P <0.01) reduce the germination rate, germination speed, germination simultaneity, normal sprout dry weight. Meanwhile scarification on one and two side were very significantly (P <0.01) increase the number of leaf sub branches and plant dry weight compared to control. Based on the results of the study it could be concluded that on of the greenhouse scale scarification on one side of the seed and on the two sides of the seed was able to increase the viability and vigor of Moringa seed.